Nucleation and Crystal Formation in Lithium Disilicate‐Apatite Glass‐Ceramic from a Combined Use of X‐Ray Diffraction, Solid‐State NMR, and Microscopy. Issue 2 (15th January 2019) - Liao, Wei‐Chih; Rampf, Markus; Dittmer, Marc; Copéret, Christophe; Höland, Wolfram
Abstract: Glass‐ceramics are multi‐phase materials that are comprised of one amorphous phase and at least one crystalline phase. Their versatile performance and properties can be engineered by alterations of the three fundamental steps – formulation and production of the amorphous base glass, nucleation, and crystallization. Efforts have been made on syntheses of glass‐ceramics with different components, yet little is known about the details of nucleation and crystallization processes that are essential for tailoring glass‐ceramic properties. Herein, we investigate the nucleation and crystallization mechanisms of a multi‐component, that is SiO2 ‐Al2 O3 ‐CaO‐Li2 O‐K2 O‐P2 O5 ‐F, glass‐ceramic system by a combined use of powder X‐ray diffraction (pXRD), solid‐state nuclear magnetic resonance (NMR), and electron microscopic (EM) techniques. The role of P2 O5 in the nucleation and crystallization processes is particularly studied. We show that the formation of lithium silicate crystals being independent of the P2 O5 ‐associated crystals, and the separation of P2 O5 phases into individual growth domains of lithium orthophosphate and fluorapatite. We also observe the non‐uniform distribution of fluorapatite particles that explains the opalescence effect of this glass‐ceramic. Abstract :